2014
DOI: 10.1149/2.0511412jes
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Electrolyte Additives in Li[Ni1/3Mn1/3Co1/3]O2(NMC)/Graphite Pouch Cells

Abstract: The effects of electrolyte additives singly or in combination on Li[Ni 1/3 Mn 1/3 Co 1/3 ]O 2 (NMC)/graphite pouch cells have been systematically investigated and compared using the ultra high precision charger (UHPC) at Dalhousie University, electrochemical impedance spectroscopy (EIS), an automated storage system, gas evolution measurements and selected long-term cycling experiments. The results of testing Li[Ni 1/3 Mn 1/3 Co 1/3 ]O 2 (NMC)/graphite pouch cells with different electrolyte additives singly or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
109
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 15 publications
0
109
0
2
Order By: Relevance
“…27 Figures 1a and 1b show a summary of the area specific charge transfer resistance (R ct ) of cells after formation and the volume of gas generated during formation, respectively, for cells with each electrolyte. The red, gray and green bars show the results for cells with PES, FEC and VC as the primary additive, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…27 Figures 1a and 1b show a summary of the area specific charge transfer resistance (R ct ) of cells after formation and the volume of gas generated during formation, respectively, for cells with each electrolyte. The red, gray and green bars show the results for cells with PES, FEC and VC as the primary additive, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic studies by Nelson et al 8 showed that 2% PES is the optimum concentration of PES for NMC111/graphite and NMC442/graphite cells. Recently, a major study of the effects of 19 electrolyte additives and their combinations on NMC111/graphite cells by Wang et al 9 showed that selected ternary or quaternary additive combinations, especially 2% PES + 1% methylene methanedisulfonate (MMDS) + 1% tris(trimethylsilyl) phosphite (TTSPi) ("PES-211") gave significant improvements in long-term cycling, CE, and charge end-point capacity slippage.…”
mentioning
confidence: 99%
“…Some promising VC-based and PES-based additive combinations 9 were selected for evaluation during long-term cycle testing at 55…”
Section: Resultsmentioning
confidence: 99%